Regional Inequality in the distribution of dentists in Saudi Arabia by sector and nationality: A 2023 National analysis under vision 2030 - Waleed Kattan (PLoS ONE, 2026)
Objective This study examines the distribution of dentists across Saudi Arabia’s regions in 2023, comparing the public and private sectors and Saudi- and non-Saudi dentists, to inform effective oral healthcare policies aligned with Vision 2030. Methods Using data from the 2023 MOH Statistical Yearbook, dentist per 10,000 people ratios were calculated across 20 health regions. Regional disparities were assessed using the Gini coefficient and Lorenz curves, which evaluated inequalities by sector (MOH versus private sector) and nationality (Saudi versus non-Saudi). Results Between 2019 and 2023, Saudi Arabia’s dental workforce experienced significant growth, reaching a density of 7.7 dentists per 10,000 people. However, regional disparities remain pronounced, with higher densities in smaller regions, such as Al-Bahah (9.0), compared to densely populated areas like Makkah (4.5). The private sector dominates dentist employment, accounting for approximately 70% of dentists, particularly in urban areas. It also exhibits significant regional distribution inequality, as indicated by a Gini coefficient of 0.60. Notably, the MOH relies heavily on non-Saudis (92%), which contrasts sharply with private-sector employment patterns, where 67% of dentists are Saudi. Conclusion Despite overall improvements in dentist density, substantial regional and sectoral disparities persist. Effective policymaking requires targeted interventions that address geographic inequalities, incentivize public sector employment, and promote Saudization to achieve Vision 2030’s goal of equitable healthcare access nationwide. These results highlight persistent inequalities in the distribution of oral healthcare. Addressing these gaps through targeted regional planning, enhanced Saudization, and balanced public–private strategies will be crucial for realizing Vision 2030’s goals of equitable access.